Memaksimalkan Hasil Belajar Santri Diyayasan Nurul Ikhsan Dengan Model Pembelajaran Yang Efektif - Eko Sudarso; Ali Zaenal; Syawaludin (Universitas Pamulang, 2023)
Various strategies that can be used to maximize student learning outcomes at the Nurul Ikhsanfoundation include an effective learning model. An educator is said to be successful andsuccessful if the students become pious and their knowledge is useful. Teachers are “relentlessheroes”. If it were not for the services and struggles of a teacher, our students would not knowletters and could not read. One of the duties of lecturers is stated in the Law on teachers andlecturers article 1 paragraph 2. Lecturers are professional educators and scientists with the maintask of transforming, developing, and disseminating science, technology, and art througheducation, research, and community service.Keywords: Maximizing learning outcomes